On Ideals of Bi-Algebras - Ahn, S. S; Ko, J. M; Saeid, Arsham Borumand (IndoMS, 2019)
In this paper, we discuss normal subalgebras in BI-algebras and obtain the quotient BI-algebra which is useful for the study of structures of BI-algebras. Moreover, we obtain several conditions for obtaining BI-algebras on the non-negative real numbers by using an analytic methods.